Cytological Detection of Iron Overload and Cytomorphometric Changes in buccal Mucosa of Βeta Thalassemia Major Patients - Nasir Karim, Ghazia Fatima, Zafar Iqbal, Tahreem Anwer, Faiz Ahmad Faiz (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: In this study, the phenomenon of oral exfoliative cytology is explored and buccal squamous cells are examined for intracytoplasmic, Prussian blue stained, iron containing granules. In addition, these buccal squamous cells are subjected to morphometric measurements of their nuclear and cytoplasmic diameter along with their ratios. Methods: It was a Descriptive, Cross sectional study including 120patients of Thalassemia Major, ranging from 4 -18 years with repeated blood transfusions and a serum ferritin level of 1000ng/ml at minimum. Scrapings were obtained from buccal mucosa for cytological examination and stained with Prussian Blue Stain. Results: The study included 45 female and 75 male patients with a mean age 11.04(± 3.81) years. 56out of 120 patients were positive for Prussian blue and thus showed 46.6% positivity. The mean cytoplasmic diameter was 50.90 (± 0.64) microns and mean nuclear diameter was 9.31(±0.53) microns. Mean Nuclear to cytoplasmic (NC) ratio was 0.182(± 0.01) and ranged from 0.165 and 0.211 microns. Conclusion: The positivity of Prussian blue in our study is clearly less than most of the quoted figures while alterations in morphometric features of buccal squamous cells are quite consistent with reported data. In our study, we observed iron containing granules not only in the cytoplasm but also on surface of cells like a clue cell dispersed outside the cell, individually or in discrete clusters and as faint bluish hue in background. Keywords: Iron overload, Cytomorphometry, buccal smear, Prussian blue, Beta Thalassemia